EMBRYONIC DEVELOPMENT OF THE HEART AND THE FORMATION OF CONGENITAL HEART DEFECTS - Ziyotdinova Dilnavo; Sharofboyeva Marjona; Sharifov Azizbek; Farmonov Shakhzod (Modern American Journals, 2025)
The embryonic development of the human heart is a complex, finely orchestrated process that begins early in gestation. It involves the transformation of simple mesodermal cells into a fully structured and functional four-chambered organ. This developmental journey includes critical steps such as the formation of the primitive heart tube, cardiac looping, chamber differentiation, septation, and the development of valves and major vessels. Disruptions in any of these stages, caused by genetic mutations, chromosomal abnormalities, or environmental factors, can lead to congenital heart defects (CHDs). CHDs represent the most common type of birth defect and vary widely in severity and anatomical presentation. Understanding the molecular and morphological mechanisms underlying heart development is essential for early diagnosis, targeted treatment, and potential prevention of congenital cardiac anomalies. Ongoing research in embryology and genetics continues to shed light on the pathogenesis of these conditions and offers new prospects for prenatal and postnatal care.
Keywords: Embryonic heart development, congenital heart defects, cardiac morphogenesis, heart tube, cardiac looping, septation, cardiovascular embryology, genetic mutations, environmental teratogens, prenatal diagnosis